Assessment of 53Mn deposition on Earth via accelerator mass spectrometry - Rodrigues Ferreira Maltez, Dario Pablo (2018)
The 53Mn flux onto Earth is a quantity relevant for different extraterrestrial and astrophysical questions. It is a proxy for related fluxes, such as supernova-produced material or interplanetary dust particles. In this work, we performed a first attempt to assess the 53Mn flux by measuring the 53Mn/10Be isotopic ratio in a 1400 L sample of molten Antarctic snow by AMS (Accelerator Mass Spectrometry). Using the 10Be production rate in the atmosphere, an upper limit of 5.5 × 103 atoms cm−2 yr−1 was estimated for the deposition of extraterrestrial 53Mn. This result is compatible with one of the two discrepant values existing in the literature.